(untitled) (Fiep Bulletin - online, 2016)
Introduction: Low back pain is usually defined as pain, discomfort, muscle tension or hardness located on the lowest part of spine, below thoracic spine and above sacrum, with or without leg pain. Objective: The objective of this article was verifying the presence of low back pain in physiotherapy students of a private college in Cascavel, Pr. Methodology: this is a n epidemiological study, with quantitative and cross cut research. The sample was compound by 95 students, female, ages between 18 and 30 years old. The researchers made a questionnaire, based on incapacity level of Oswestry, 10 minutes screening trial of Hendler and Roland Morris questionnaire, applied from May 19th 2014 until June 06th 2014. The results were analyzed on Microsoft Office Excel 2013 and statistics evaluation was done on SPSS15.0 Software. Results: We observed that 60,2% of the students had low back pain and intensity fluctuated from 3,6 +/-1,4 weak to medium. 39,4% have difficulty to execute squat exercise at the gym. 62,4% of the students have low back pain when they remain seated for a period longer than 2 hours. Conclusion: this study showed the presence of low back pain in 60,2% of the students and possible reasons are remain seated and the gym exercises when made in an incorrect way.